ARSITEKTUR RUMAH ADAT MINAHASA DI KELURAHAN WOLOAN KECAMATAN TOMOHON BARAT KOTA TOMOHON - Kolibu, Syutrika Ivana Irlani; Matheosz, Jenny Nelly; Mulianti, Titiek (HOLISTIK, Journal Of Social and Culture, 2018)
Indonesia has culture and a people who different in all corners of the country. Basically a regions having specific characteristic which special, so that an areas or local utility must have different characteristics from to the region or other areas. With so many is various so that culture in Indonesia grown very much in various regions, because basically culture is important will benefits and could be identity or specific characteristic which distinguish a territory culture. One of culture who still stay there until now is traditional house. Housing is its importance as dwellings activity vernacular by family.This research using the methodology that are descriptive qualitative the aims to describe exactly the properties of a individual, the state of, a symptom or frequency certain the connection between symptoms and symptom of other in society.Meaning that is implied in suggests an idea traditional house creative culture with a characteristic as also in Minahasa traditional house we all know about that the traditional home is the imprint of our ancient ancestors were. The creativity of the Minahasa community made the house customary is a commodity that can produce income especially potters in Woloan Village Tomohon Barat District Tomohon City. Often see an order from outside the area foreign until, with size on demand consumer but does not standard change Minahasa traditional house. Marketed with houses are so much higher admiration people who were in outside the Minahasa region to appreciate the work of one of the people.Keywords: traditional house, meaning, culture